Targeting the Wnt signaling pathway through R-spondin 3 identifies an anti-fibrosis treatment strategy for multiple organs - Zhang, Mingjun; Haughey, Michael; Wang, Nai Yu; Blease, Kate; Kapoun, Ann M.; Couto, Suzana; Belka, Igor; Hoey, Timothy; Groza, Matthew; Hartke, James; Bennett, Brydon; Cain, Jennifer; et al. (PLoS ONE, 2020)
The Wnt/β-catenin signaling pathway has been implicated in human proliferative diseases such as cancer and fibrosis. The functions of β-catenin and several other components of this pathway have been investigated in fibrosis. However, the potential role of R-spondin proteins (RSPOs), enhancers of the Wnt/β-catenin signaling, has not been described. A specific interventional strategy targeting this pathway for fibrosis remains to be defined. We developed monoclonal antibodies against members of the RSPO family (RSPO1, 2, and 3) and probed their potential function in fibrosis in vivo. We demonstrated that RSPO3 plays a critical role in the development of fibrosis in multiple organs. Specifically, an anti-RSPO3 antibody, OMP-131R10, when dosed therapeutically, attenuated fibrosis in carbon tetrachloride (CCl4)-induced liver fibrosis, bleomycin-induced pulmonary and skin fibrosis models. Mechanistically, we showed that RSPO3 induces multiple pro-fibrotic chemokines and cytokines in Kupffer cells and hepatocytes. We found that the anti-fibrotic activity of OMP-131R10 is associated with its inhibition of β-catenin activation in vivo. Finally, RSPO3 was found to be highly elevated in the active lesions of fibrotic tissues in mouse models of fibrosis and in patients with idiopathic pulmonary fibrosis (IPF) and nonalcoholic steatohepatitis (NASH). Together these data provide an anti-fibrotic strategy for targeting the Wnt/β-catenin pathway through RSPO3 blockade and support that OMP-131R10 could be an important therapeutic agent for fibrosis.
CRIS-Team Scopus Importer:2020-03-20